Following in their footsteps: An analysis of the impact of successive migration on rural household welfare in Ghana - Eva-Maria Egge; Julie A. Litchfield (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
The decision to migrate is often influenced by the experience of earlier migrants from one's household. Earlier migrants provide information on likely opportunities and potential risks and can offer support at destination to later migrants. We explore patterns of migration within rural households and the impact that these later migrants have on household welfare outcomes. Specifically, we use a household panel survey collected in 2013 and 2015 in rural areas of Ghana. We exploit the panel nature of the data and a weighting method to overcome sources of bias. Welfare is measured with an asset index of housing quality. We find that more recent or "new" migrants are more likely to be from a younger generation, they face lower migration costs, and few of them remit. We find no effect of sending a new migrant on the asset index. We conclude that the different nature of migration of new migrants implies neither an economic gain for the household nor a loss. The reason for the former is that the more recent migrants remit less or not at all compared to earlier waves of migrants and the reason for the latter is that migration becomes less costly with prior experience.
Keywords: R23; C38; D10; 330; migration; Ghana; asset index; multiple correspondence analysis; entropy balancing weights